Fabrication and Characterization of Nickel Chloride Doped PMMA Films - Wasan A. Al-Taa’y; Saad F. Oboudi; Emad Yousif; Mohammed Abdul Nabi; Rahimi M. Yusop; Darfizzi Derawi (Advances in Materials Science and Engineering)
Films of PMMA and PMMA doped with NiCl2 with different contents were prepared using the casting technique. The optical properties of all films were investigated using spectrophotometric measurements of absorbance and transmittance in the wavelength range 200–800 nm. The change of the calculated values of the optical energy gaps with increasing NiCl2 content has been interpreted in terms of the structural modifications of the PMMA matrix. The optical energy gap decreased from 3.6 to 3.05 eV with increasing the NiCl2 concentration to 0.4%. The effect of doping on the optical constants of films such as refractive index, extinction coefficient, real and imaginary parts of dielectric constant, optical conductivity, and skin depth has been reported. All these constants were increased with increasing NiCl2 concentration with the exception of skin depth which is different result.